Cerebrospinal Fluid (CSF) Exchange with Artificial CSF Enriched with Mesenchymal Stem Cell Secretions Ameliorates Experimental Autoimmune Encephalomyelitis - Valitsky, Michael (Int J Mol Sci, 2019)
The complexity of central nervous system (CNS) degenerative/inflammatory diseases and the lack of substantially effective treatments point to the need for a broader therapeutic approach to target multiple components involved in the disease pathogenesis. We suggest a novel approach directed for the elimination of pathogenic agents from the CNS and, in parallel, its enrichment with an array of neuroprotective substances, using a “cerebrospinal fluid (CSF) exchange” procedure, in which endogenous (pathogenic) CSF is removed and replaced by artificial CSF (aCSF) enriched with secretions of human mesenchymal stem cells (MSCs). MSCs produce a variety of neuroprotective agents and have shown beneficial effects when cells are transplanted in animals and patients with CNS diseases. Our data show that MSCs grown in aCSF secrete neurotrophic factors, anti-inflammatory cytokines, and anti-oxidant agents; moreover, MSC-secretions-enriched-aCSF exerts neuroprotective and immunomodulatory effects in neuronal cell lines and spleen lymphocytes. Treatment of experimental-autoimmune-encephalomyelitis (EAE) mice with this enriched-aCSF using an intracerebroventricular (ICV) CSF exchange procedure (“CSF exchange therapy”) caused a significant delay in the onset of EAE and amelioration of the clinical symptoms, paralleled by a reduction in axonal damage and demyelination. These findings point to the therapeutic potential of the CSF exchange therapy using MSC-secretions-enriched-aCSF in inflammatory/degenerative diseases of the CNS.